2016
DOI: 10.1039/c5ra26523a
|View full text |Cite
|
Sign up to set email alerts
|

New fluorene-based chiral copolymers with unusually high optical activity in pristine and annealed thin films

Abstract: Polyfluorene (PF)-based chiral alternating copolymers, i.e., PFPh and PFTh, were successfully synthesized to obtain high circular dichroism (CD) in pristine thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 21 publications
3
25
0
2
Order By: Relevance
“…1000 mdeg, see the black line in the inset of Fig. 5) 21,42 arises from the cholesteric arrangement of the polymer chains 43–45 . The CD spectrum of the polymer will also experience a pressure-induced periodic shift because of the propagation of the acoustic phonon inside the film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1000 mdeg, see the black line in the inset of Fig. 5) 21,42 arises from the cholesteric arrangement of the polymer chains 43–45 . The CD spectrum of the polymer will also experience a pressure-induced periodic shift because of the propagation of the acoustic phonon inside the film.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis and characterization of the chiral PFPh and PFBT were described recently 21 . Cholesteric copolymer thin films were produced by spin-coating a filtered 7.5 mg ml −1 solution of each polymer in a chlorobenzene-chloroform mixture (1:9 by volume) on thoroughly cleaned and ozonized Duran glass slides (thickness 1 mm) for one minute at 1000 or 500 rpm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Intrinsically chiral PFBT (c-PFBT) copolymer with a number average molar weight ( M n ) of 7.46 kg mol −1 and polydispersity (PDI) of 2.44 was prepared via Suzuki polycondensation from 2,7-bispinacoyl-9,9-bis(( S )-3,7-dimethyloctyl)fluorene boronic ester, 3,6-dibromothiadiazole and 2-pinacoyl-9,9-bis(( S )-3,7-dimethyloctyl)fluorene boronic ester and then purified afterwards 17 , 18 . A solution of c-PFBT in a chlorobenzene:chloroform mixture (1:9 by volume, concentration 7.5 mg ml −1 ) was spin-coated on thoroughly cleaned 1 mm-thick borosilicate glass slides.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Chen and co-workers have shown that chiral oligo­(fluorenes) , exhibit highly ordered chiral liquid crystalline phases such as cholesterics in annealed films with g -values >0.1. The cholesteric ordering has been mainly observed for poly­(fluorene) homopolymers, , copolymer, and poly­( p -phenyleneethynylene)­s which exhibited g -values ranging from 0.1 to 1 in annealed thin-films. Unlike the metal complexes discussed previously, the chiral poly­(fluorene)­s , and poly­(thiophene)­s show a strong film-thickness dependence of g abs , indicating that the long-range cholesteric ordering dictates the g -value in such systems.…”
Section: Introductionmentioning
confidence: 99%